BMIm HCO3: an ionic liquid with carboxylating properties. Synthesis of carbamate esters from amines. (24th October 2016) - Di Nicola, A.; Arcadi, A.; Rossi, L.
Abstract : BMIm HCO3 is an ionic liquid obtained by the ion-exchange method showing interesting carboxylating properties. Abstract : 1-Butyl-3-methylimidazolium hydrogen carbonate (BMIm HCO3 ) was used as an ionic liquid with carboxylating properties able to convert, in the presence of an alkyl halide, amines into the corresponding carbamate esters. Moderate to good yields of carbamates were obtained according to the nature of the amine and the alkylating agent.